Langkah-Langkah Penanganan Terhadap Tindak PidanaPencurian Dengan Pemberatan(Studi Kasus Di Polres Karanganyar) - Fitriyani, Dewi, Dr. Natangsa Surbakti, S.H., M.Hum (2016)
The purpose of this study was to determine the process and the results of the investigation of criminal theft by weighting against the perpetrators of the theft of motor vehicles in Karanganyar district police as well as the obstacles facing investigators This research includes empirical legal research. Research conducted at the Police Resort (Police) Karanganyar. The data source using primary data. Data were analyzed using qualitative analysis. The results showed that: The process of criminal investigations against the perpetrators of theft by weighting of motor vehicle theft in Karanganyar district police began with the investigation stage with a view to determining whether an event alleged criminal act actually occurs. The next stage of the investigation, namely: to receive reports, perform the first act (check the truth of the report or the complaint with a check on the scene), arrest and detention, seizure, fingerprinting and photographing of suspects, examination of suspects and witnesses, and the end is drawing up Minutes the probe to be delegated to the Attorney General. The obstacles facing investigators Karanganyar Police in dealing with the crime of theft by pemberatanadalah lack of evidence and witnesses to the incident of theft that occurred. Police mensiasatinya to optimize the role of the community as a source of information on the various events theft.